ACETAMINOPHEN AND DIPHENHYDRAMINE AS MEDICATION PRETRANSFUSION THE INCIDENCE OF FEBRILE NON-HAEMOLYTIC TRANSFUSION REACTION PLATELET RECIPIENTS - Arshanti, Pudya Lestari (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACTBackground. Blood transfusion can save lives, patients get the benefit but also the risk of transfusion-related. Febrile non-haemolytic transfusion reaction (FNHTR) most frequently found and have similar symptoms of other transfusion reactions, causing delays in transfusion and decrease the quality of life. Platelet recipients have a higher incidence risk FNHTR than recipients of other blood products. Medications pre-transfusion acetaminophen and diphenhydramine reduce the incidence FNHTR.Methods. The study was conducted from May to November 2010 Internal Medicine Wards, Dr. Sardjito Hospital, Yogyakarta using the method of double-blind randomized controlled trial. Inclusion criteria were first recipient of random donor non leucodepleted platelets in thrombocytopenia malignant patients and willing to participate. Exclusion criteria were fever is when will transfusions or in 2x24 hours, allergies of acetaminophen and diphenhydramine, acetaminophen and diphenhydramine consumption in the last 6 hours, the consumption of continuous corticosteroids, history of transfusion reactions and critical conditions/sepsis. Assessment of the incidence FNHTR 15 minutes before transfusion to 4 hours after transfusion. Medication group will receive a capsule containing 650 mg acetaminophen and 25 mg diphenhydramine dissolved in 5 ml 0.9% NaCl intravenously. The control group received a placebo. Drugs are given 30 minutes before the first transfusion bag. Data were analyzed using Chi-square test and p <0.05 was considered statistically significant.Results. Thirty-two patients met the criteria, 15 patients (46.87%), medication group and 17 (53.13%) patients of control group. Eleven (31.43%) patients had FNHTR, 8 (47.06%) patients of control group and 3 (20%) patients. There are differences in the proportion of incident FNHTR in both groups although not statistically significant (P = 0.04). Every patient has different risk factors on parity, history of transfusion, history of FNHTR and the long of platelet storage. Conclusion. As pre-transfusion medications, Acetaminophen 650 mg and diphenhydramine 25 mg reduced the incidence of FNHTR compared to placebo in the first platelet recipients in malignancy Key words: Acetaminophen, diphenhydramine, medication pretransfusion, FNHTR.Â